ANALYSIS OF THE VALUES OF CHARACTER EDUCATION IN THE THEMATIC TEXTBOOK VII "EVENTS IN LIFE" FOR CLASS V STUDENTS - Rosdiana; Muhammad Yaumi; Nurhikmah; Suharti (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to describe the integration of character education values and the feasibility of learning materials for character education values in the thematic textbook theme VII, "Events in Life," for class V students. This study was qualitative with a discourse analysis research design. The data sources in this study were the 7th-theme "Events in Life" of the thematic textbook for class V students at MIS Muhammadiyah Gowa. The instruments used were interview guidelines and data cards. Data processing and analysis techniques were carried out in three stages: data condensation, data presentation, data verification and conclusion drawing. The results showed that there were 14 values of character education in the thematic book, religious character values, tolerance, discipline, hard work, creativity, democratic, curiosity, national spirit, love for the homeland, friendly/communicative, peace-loving, fond of reading, social care, and responsibility. Three main things were found, which indicated that the book has the feasibility to be studied by students, namely: (1) increasing faith and piety, (2) character and mastery of science and technology, and (3) increasing sensitivity and concern.